Comparing the effects of vein finder technology and traditional venipuncture on pain and behavioural states in preterm infants: a quasi-experimental study - Salwa Sayed; Basma Rabea Abdel Sadek; Rasha Rady El Said (BMJ Paediatrics Open)
Introduction Preterm infants frequently undergo venipuncture, causing pain and distress. Traditional methods rely on clinical expertise, often leading to multiple attempts and prolonged procedures. Vein finder technology aims to improve success rates and reduce discomfort, yet its effects on pain perception and behavioural states in preterm infants remain underexplored.Aim This study aimed to compare the effects of using a vein finder versus the traditional venipuncture method on pain perception and behavioural responses among preterm infants in neonatal intensive care units (NICUs).Methods A quasi-experimental study was conducted in two governmental hospitals in Egypt, involving 124 preterm infants (62 in the vein finder group and 62 in the traditional method group). A pre-designed questionnaire was used to collect demographic and clinical data. Pain and behavioural responses were assessed using two validated tools: the Neonatal Infant Pain Scale (NIPS) and the Neonatal Behavioural State Scale. Data were collected over a 6-month period from March 2024 to August 2024.Results The vein finder group had significantly lower pain scores (mean NIPS score: 5.75±1.11 vs 6.83±1.35; mean difference: −1.08, p<0.01) and shorter crying durations (mean: 2.94±0.25 min vs 5.61±1.10 min; p<0.01). Behavioural states improved, with longer durations in deep sleep (15.36±3.12 min vs 4.57±1.65 min) and reduced active alert states (4.30±1.74 min vs 10.95±3.28 min; p<0.01). First-attempt success rates were higher (87.1% vs 46.8%), and fewer complications (eg, phlebitis, infiltration) were reported in the vein finder group.Conclusion The use of vein finder technology may significantly reduce pain, improve behavioural states and enhance procedural success in preterm infants compared with traditional venipuncture methods. These findings suggest that incorporating this technology into NICUs practice might benefit patient comfort and clinical efficiency.